Structural and functional studies on human enzymes involved in hydrogen sulfide breakdown - Gutierres, André Luís Teixeira (2017)
In human physiology, hydrogen sulfide (H2S), a small gaseous molecule that diffuses across aqueous and hydrophobic milieu, has been shown to team up with NO and CO as the third ‘gasotransmitter’. The still growing number of physiological processes shown to be regulated by H2S includes blood flow, cellular stress response, inflammation, immune defense, apoptosis and energy metabolism. Consequently, disturbed H2S metabolism is associated with numerous human pathologies, from cardiovascular and inflammatory disorders, to neurodegeneration and cancer. As any other reactive signaling molecule, H2S homeostasis requires a fine balance between its synthesis and breakdown. One of the enzymes involved in the synthesis of H2S in humans is cystathionine β-synthase (CBS), one key enzyme of the transsulfuration pathway. H2S breakdown relies on a mitochondrial pathway involving a sulfide:quinone oxidoreductase (SQR), a sulfur dioxygenase, Rhodanese, and a sulfite oxidase. O2-dependent H2S consumption may be primarily controlled by its efficient catabolism via SQR, which may be a key regulator in switching off H2S signaling by consuming it. Although numerous studies have focused on the functional analysis of H2S catabolism components, there is a paucity of structural data to support i) the understanding of functional/physiological data, and ii) the discovery and design of modulatory compounds with potential pharmacological interest. The aim of this dissertation was to characterize from a structural and functional viewpoint human enzymes involved in H2S metabolism, employing different biophysical methodologies. Recombinant human Rhodanese was expressed in Escherichia coli and purified with a yield of 2mg/L of culture. By a combination of DSF (Differential Scanning Fluorimetry), CD (Circular Dichroism) and SAXS (Small Angle X-ray Scattering) studies, it was observed that cysteine, thiosulfate and alliin affects Rhodanese structure. This information was used into crystallization trials but without getting any Rhodanese crystals. The recombinant human SQR expression and purification was unsuccessful, precluding any further studies, and being still under development. In parallel with work on the sulfide oxidizing unit, structural studies were carried out with recombinant human cystathionine β-synthase. In particular, the crystallographic structure of the disease-causing variant CBS P49L was obtained at 2.8 Å resolution, showing very subtle differences from the WT CBS structure. However, these do not completely explain the functional impact of this mutation and its pathogenicity.